Genetic variation of the RASGRF1 regulatory region affects human hippocampus-dependent memory - Barman, Adriana; Assmann, Anne; Richter, Sylvia; Soch, Joram; Schütze, Hartmut; Wüstenberg, Torsten; Deibele, Anna; Klein, Marieke; Richter, Anni; Behnisch, Gusalija; Düzel, Emrah; Zenker, Martin; et al. (Frontiers in Human Neuroscience, 2014)
The guanine nucleotide exchange factor RASGRF1 is an important regulator of intracellular signaling and neural plasticity in the brain. RASGRF1-deficient mice exhibit a complex phenotype with learning deficits and ocular abnormalities. Also in humans, a genome-wide association study has identified the single nucleotide polymorphism (SNP) rs8027411 in the putative transcription regulatory region of RASGRF1 as a risk variant of myopia. Here we aimed to assess whether, in line with the RASGRF1 knockout mouse phenotype, rs8027411 might also be associated with human memory function. We performed computer-based neuropsychological learning experiments in two independent cohorts of young, healthy participants. Tests included the Verbal Learning and Memory Test (VLMT) and the logical memory section of the Wechsler Memory Scale (WMS). Two sub-cohorts additionally participated in functional magnetic resonance imaging (fMRI) studies of hippocampus function. 119 participants performed a novelty encoding task that had previously been shown to engage the hippocampus, and 63 subjects participated in a reward-related memory encoding study. RASGRF1 rs8027411 genotype was indeed associated with memory performance in an allele dosage-dependent manner, with carriers of the T allele (i.e. the myopia risk allele) showing better memory performance in the early encoding phase of the VLMT and in the recall phase of the WMS logical memory section. In fMRI, T allele carriers exhibited increased hippocampal activation during presentation of novel images and during encoding of pictures associated with monetary reward. Taken together, our results provide evidence for a role of the RASGRF1 gene locus in hippocampus-dependent memory and, along with the previous association with myopia, point towards pleitropic effects of RASGRF1 genetic variations on complex neural function in humans.